Consumer Decision Preferences for Halal-Labeled Cosmetic Products in the Perspective of Islamic Economics - Febby Fitri Adriansyah; Neng Kamarni (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of socioeconomic factors, price, and religiosity on the consumption decisions of halal-labeled cosmetic products with consumer trust as a mediating variable among Muslim female students at Andalas University. The research method used a quantitative approach with data collection techniques through questionnaires to 100 respondents selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM-PLS) with the help of the SmartPLS application. The results show that price and religiosity have a positive and significant effect on consumer trust and consumption decisions, while socioeconomic factors have no significant effect. In addition, consumer trust is unable to significantly mediate the influence of independent variables on consumption decisions. The implications of this study indicate that religiosity and price, which reflect product quality, are the main determinants in forming consumption decisions of halal cosmetic products among Muslim consumers.